Annotated bibliography of Mindanao studies. (Mindanao Studies Consortium Foundation, 2005)
This book is a collection of annotated bibliographies of Mindanao studies and directory of researchers, writers and resources centers in Mindanao. This book is the first volume of the four volume series which focuses on the fields of education, science and technology, information technology, engineering and food technology (ST). This is a useful tool as Mindanao endeavors to respond to societal challenges in the context of peace and development. This book will also serve as a guide to future researchers in Mindanao, where studies and research are mostly focused at.